CHEMICAL COMPOSITION AND AMINO ACID PROFILE OF FRESH AND STEAMED COBIA (Rachycentron canadum L.) - Nurjanah Nurjanah; Ruddy Suwandi; Taufik Hidayat; Vini Oktorina (University of Sultan Ageng Tirtayasa, 2020)
Cobia (Rachycentron canadum) is economically important fish with good prospects because of fast growing and easily cultured. Cobia is usually processed by many methods including steaming. The purposes of this research were to determine the effect of steaming process on proximate and amino acids composition. The chemical composition of fresh and steamed cobia’s meat were determined by proximate analysis. Amino acid compositions of fresh and steamed cobia’s meat were measured using HPLC (high performance liquid chromatography). Steaming process reduced 11.31% of water, 1.06% of ash, 26.04% of fat, and 9.11% of protein. Fresh and steamed cobia’s meat contained 17 amino acids consisting of 9 essential amino acids and 8 nonessential amino acids. The highest essential amino acid in fresh cobia’s meat was arginine (2,262 mg/100 g) and the highest nonessential amino acid was glutamic acid (3,894 mg/100 g). Steaming process reduced amino acids generally. The highest essential amino acid in steamed cobia’s meat was leucine (1,379 mg/100 g) and the highest nonessential amino acid was glutamic acid (2,370 mg/100 g). Taurine content of fresh cobia’s meat was 120.84 mg/100 g and changed into 94.33 mg/100 g after steaming process.